Estudo do desempenho do sistema fotovoltaico conectado à rede: estudo de caso: escritório verde da Universidade Tecnológica Federal do Paraná - Campus Curitiba - Bittencourt, Cezinando (2013)
Distributed generation is a trend as an alternative source of power generation, motivating the development of this work, wich was done using the Grid-Connected Solar PV System of Green Office wich belongs to Federal Technological University of Paraná, Curitiba Campus. This research was carried out on three pillars, the first to analyze the quality of power delivered to the load with the photovoltaic connected and disconnected from the grid; the second point dicussed was the analysis of the performance of the Grid-Connected Solar PV Systems of Green Office in 2013, relative to the merit indexes (Final Yield, Performance Ratio and Capacity Factor); and the third shows the comparison of the means of encouraging the use of PV system in Brazil, Germany, Italy, Spain, USA, China, Japan and India. Relative to the merit indexes, there was a decrease in Productivity and Capacity Factor in 2012, however there was an improvement in overall performance when cleaning the photovoltaics modules. Regarding the quality of energy there is a trend in increased tension at the point of connection to load, when the inverter is in operation, as well as a decrease in the Total Harmonic Voltage Distortion (THDu).